Aedes aegypti (Diptera: Culicidae): evaluation of natural long-lasting materials containing pyriproxyfen to improve control strategies - Seccacini, Emilia Ana (2014)
Natural materials such as beeswax or a paraffin/stearin mixture containing pyriproxyfen and used as a slow release formulation may convert any breeding place into a larvicidal ovitrap for Aedes aegypti (L.) control. Effectiveness and residual activity of beeswax and paraffin/stearin 1:1 discs containing from 10−5 to 10−1 % pyriproxyfen and sticked at the bottom of plastic jars were evaluated for adult emergence inhibition (EI) on late 3rd or early 4th instar A. aegypti larvae. At the initial time t = 0, the EI was 100 % for vessels containing beeswax or paraffin/stearin 1:1 discs containing up to 10−4 % pyriproxyfen. For the lowest pyriproxyfen concentration of 10−5 %, paraffin/stearin mixture gave a higher EI% value than beeswax (100 and 50 %, respectively). Jars were kept at room temperature, and water was totally replaced every 15 days. Bioassays for residual activity repeated monthly showed that at 30 days and for pyriproxyfen 10−5 % and both matrices, the EI values were low and comparable to control values. For pyriproxyfen 10−4 %, EI remained above 95 % for at least 90 days and around 75 % up to 180 days. The EI values are always higher for paraffin/stearin mixture than for beeswax. For all other higher concentrations, 100 % EI was obtained at least during 300 days. In a semi-field trial, paraffin/stearin/sand O-rings (2:1:2), containing pyriproxyfen 1 %, were sunken in 200-l water-storage tanks and held outdoors in a shadow place. After 72 h, a 250-ml aliquot was taken (t = 0) obtaining 100 % EI. Water level was completed to 200 l every 15 days and bioassays repeated monthly as before. Residual activity remains with 100 % EI at least for 6 months.